2018
DOI: 10.1007/s11605-017-3617-5
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Surgical Resection of the Primary Tumor in Patients Undergoing Chemotherapy for Stage IV Colorectal Cancer with Unresected Metastasis

Abstract: Our results show that in patients with synchronous unresected stage IV colorectal adenocarcinoma undergoing single- or multi-agent chemotherapy, after adjusting for confounding variables, definitive resection of the primary site was associated with improved overall survival. Large randomized controlled trials are needed to determine if there is a causal relationship between surgery and increased overall survival in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…CEA levels positive is associated with worse prognosis and the prognosis of patients with lymphatic metastasis might be worse than those without. Currently, there exists controversy regarding the long-term benefit of primary tumor resection in stage IV and many prior studies suggest there is no benefit to survival with primary tumor resection (15,16) , while others suggest a clinical benefit with surgical resection (17)(18)(19) . In our study, we found the patients could significantly be beneficial from primary tumor resection with remarkable improvement of CSS.…”
Section: Discussionmentioning
confidence: 99%
“…CEA levels positive is associated with worse prognosis and the prognosis of patients with lymphatic metastasis might be worse than those without. Currently, there exists controversy regarding the long-term benefit of primary tumor resection in stage IV and many prior studies suggest there is no benefit to survival with primary tumor resection (15,16) , while others suggest a clinical benefit with surgical resection (17)(18)(19) . In our study, we found the patients could significantly be beneficial from primary tumor resection with remarkable improvement of CSS.…”
Section: Discussionmentioning
confidence: 99%
“…More clinical studies focus on the benefits of primary tumor resection alone. Although there are still controversies at present [13,14], most of the existing clinical studies show that the resection of the primary tumor alone can not only reduce the incidence of local complications [15], but also seem to benefit the survival of patients [7,16,17]. However, there are limited data regarding the effect of primary tumor radiotherapy in stage IV unresectable rectal or rectosigmoid cancer, and most of these studies are mainly observing the palliative effect [18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…More clinical studies focus on the benefits of primary tumor resection alone. Although there are still controversies at present [16,17], most of the existing clinical studies show that resection of the primary tumor alone can not only reduce the incidence of local complications [18] but also seems to be beneficial in terms of patient survival [11,19,20]. However, there are limited data regarding the effect of primary tumor radiotherapy in stage IV unresectable rectal or rectosigmoid cancer, and most of these studies mainly observed the palliative effect [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%